2013
DOI: 10.1002/j.0022-0337.2013.77.3.tb05481.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Awareness of Croatian Dentists Concerning Patients’ Confidentiality and Privacy

Abstract: Conidentiality and privacy have always been a vital part of the health care provider-patient relationship. The aim of this study was to identify and analyze the knowledge, attitudes, and awareness of dentists in Croatia concerning patients' conidentiality and privacy and to determine the degree to which they were protecting patients' conidentiality and privacy in everyday practice. Survey data were collected from seventy of the approximately 4,000 dentists in Croatia who had been randomly selected using the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…In other studies, Budimir et al [21] showed that Croatian dentists have limited knowledge of dental regulations, and the awareness of patients’ rights is imperfect. Similarly, Tahani et al [12] reported that over 74% of dentists in Isfahan city, the Islamic Republic of Iran, have poor knowledge of dental regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, Budimir et al [21] showed that Croatian dentists have limited knowledge of dental regulations, and the awareness of patients’ rights is imperfect. Similarly, Tahani et al [12] reported that over 74% of dentists in Isfahan city, the Islamic Republic of Iran, have poor knowledge of dental regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study revealed that years of experience were not a significant factor affecting the knowledge of dental regulations, newer generations of dentists with experience less than 9 years have somewhat better knowledge compared to dentists who have been working for 9 years or more. Likewise, Budimir et al [21] showed that years of experience did not affect the overall dental ethics among dentists; however, a single ethical issue was significantly more common among dentists with fewer years of practice. These findings differ from that of Tahani et al [12] who found that dentists with more years of experience (≥9 years) have a significantly higher knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…The present study postulates poor knowledge attributed to the inadequate curriculum, poor research interest, insufficient facilities, lack of funds and training, limited time period, inadequate infrastructure, etc., These findings were found to be similar with previous studies carried out by the different scientists. [ 13 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Os profissionais acessam informações pessoais confidenciais de pacientes para entender seus problemas de saúde, e tais informações são de fato confidenciais, determinando que aqueles que a possuem têm a responsabilidade de protegê-las de divulgação para alheios (BUDIMIR et al, 2013). A contínua busca por melhorias e disponibilização de novos produtos por parte das instituições levaram vários setores a investir em sistemas de informação e tecnologia na área da saúde.…”
Section: )unclassified